A new species of Odorrana (Amphibia: Anura: Ranidae) from Vietnam - Pham, Cuong The; Nguyen, Truong Quang; Le, Minh Duc; Bonkowski, Michael; Ziegler, Thomas (Zootaxa, 2016)
A new species of Odorrana is described from the karst forests in northeastern Vietnam based on morphological differences and molecular divergence. Morphologically, the new species is distinguishable from its congeners on the basis of a combination of the following diagnostic characters: (1) size large (SVL 85.9–91.6 mm in males, 108.7–110.1 mm in females); (2) head longer than wide; (3) vomerine teeth present; (4) external vocal sacs absent; (5) snout short (SL/SVL 0.16–0.17); (6) tympanum large (TD/ED 0.70 in males, 0.68 in females); (7) dorsal surface of head and anterior part of body smooth, posterior part of body and flanks with small tubercles; (8) supratympanic fold present; (9) dorsolateral fold absent; (10) webbing formula I0–0II0–0III0–1/2IV1/2–0V; (11) in life, dorsum green with dark brown spots; (12) flanks greyish brown with dark brown spots; (13) throat and chest grey, underside of limbs with large dark brown spots, edged in white, forming a network. In the phylogenetic analyses, the new species is unambiguously nested within the O. andersonii group, and placed as the sister taxon to O. wuchuanensis.